The Relationship between strategic information system and business strategies in Malaysia - Md. Zabid Abdul Rashid; Saadiatul Ibrahim; Samsinar Md. Sidin (Penerbit Universiti Kebangsaan Malaysia, 2003)
The relationship between strategic information system and business strategy of the firm has often been raised among managers. This paper examines the nature and extent of the relationships between strategic information system and business strategy pursued by the firms. A structured questionnaire was developed and self-administered to managers in the capital city, Kuala Lumpur. A total of 86 usable responses were used to analyse the results of the study. The findings show that there were five types of strategic information system used by Malaysian firms: accounting information system, finance information system, marketing information system, management information system and general information system. The business strategies pursued were focus strategy, cost leadership strategy and differentiation strategy. Empirical evidence detected a relationship between the strategic information system used and the business strategy adopted. There were also significant differences between each of the business strategies pursued and type of strategic information system used by the firms. The implications of the findings are also discussed.